2017
DOI: 10.1002/2017jd026865
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Temporal and Spatial Trends in Sulfate and Organic Mass Concentrations Measured in the IMPROVE Monitoring Program

Abstract: Recent modeling and field studies have highlighted a relationship between sulfate concentrations and secondarily formed organic aerosols related to isoprene and other volatile biogenic gaseous emissions. The relationship between these biogenic emissions and sulfate is thought to be primarily associated with the effect of sulfate on aerosol acidity, increased aerosol water at high relative humidities, and aerosol volume. The Interagency Monitoring of Protected Visual Environments (IMPROVE) program provides aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 56 publications
3
76
1
Order By: Relevance
“…By 2050, total PM 2.5 concentrations are projected to decrease primarily due to expected reductions in anthropogenic emissions in both the RCP4.5 and RCP8.5 scenarios (Figure ). The reductions shown here are most notable in the eastern United States, particularly in the Ohio River Valley, consistent with recently observed downward trends in this region (e.g., Malm et al, ; U.S. EPA, ). In our RCP4.5 scenario simulations, PM 2.5 concentrations will continue to decrease by 2100; however, in the RCP8.5 scenario, several areas in the western United States, northeastern United States, and southeastern United States are projected to have higher concentrations compared to the early 21st century (2000).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By 2050, total PM 2.5 concentrations are projected to decrease primarily due to expected reductions in anthropogenic emissions in both the RCP4.5 and RCP8.5 scenarios (Figure ). The reductions shown here are most notable in the eastern United States, particularly in the Ohio River Valley, consistent with recently observed downward trends in this region (e.g., Malm et al, ; U.S. EPA, ). In our RCP4.5 scenario simulations, PM 2.5 concentrations will continue to decrease by 2100; however, in the RCP8.5 scenario, several areas in the western United States, northeastern United States, and southeastern United States are projected to have higher concentrations compared to the early 21st century (2000).…”
Section: Resultssupporting
confidence: 91%
“…By 2050, total PM 2.5 concentrations are projected to decrease primarily due to expected reductions in anthropogenic emissions in both the RCP4.5 and RCP8.5 scenarios (Figure 3). The reductions shown here are most notable in the eastern United States, particularly in the Ohio River Valley, consistent with recently observed downward trends in this region (e.g., Malm et al, 2017;U.S. EPA, 2012).…”
Section: Projections Of Future Pm and Fire Pm In The United Statescontrasting
confidence: 93%
“…The OC term as an indicator species appears to play a greater role at the OLF and UAH sites, and despite its higher mass fraction, a lesser role at the forested CTR site. Again, this suggests that the majority of the organic mass in the region could be due to anthropogenic sources rather than biogenic emissions, and supports recent findings suggesting the formation of OC and SO 4 2− in PM 2.5 are linked (Malm et al, ; Schichtel et al, ). The OC multiplier can also be interpreted as reflecting the amount of oxidation within the POM.…”
Section: Results I: Chemical and Optical Properties For Core Sitessupporting
confidence: 87%
“…While the formation of organosulfate SOA can explain some of the correlation, Zheng et al (), suggested that the majority of the OC at the SEARCH sites in the summer months is due to diesel emissions and not biogenic emissions, which would also lead to a connection between SO 4 2− and SOA within the PM 2.5 mass, although the research of Zheng et al () was performed prior to the switch to ultralow sulfur diesel fuel post 2006, which may render their proposed link less viable (https://www.epa.gov/diesel-fuel-standards/diesel-fuel-standards-and-rulemakings; last accessed 15 March 2018). Similarly, Malm et al () found a significant decrease in SOA concentrations corresponding to declines in SO 4 2− since 2001, suggesting a dependence of the SOA formation mechanisms on SO 4 2− PM 2.5 concentrations. Thus, it is not completely correct to assume sulfate and OC as orthogonal components of the PM 2.5 mass.…”
Section: Results I: Chemical and Optical Properties For Core Sitesmentioning
confidence: 79%
See 1 more Smart Citation